Coinfection of COVID-19 and dengue: a case report - Fx. Wikan Indrarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Dengue hemorrhagic fever (DHF) and corona virus disease 2019 (COVID-19) are two viral infectious diseases that can occur simultaneously and have the potential to complicate each other. Therefore, sustained attention to this phenomenon is required. A 9 y.o. boy was diagnosed with dengue and COVID-19 at the Panti Rapih Hospital in Yogyakarta, Indonesia, in the early phase of the COVID-19 pandemic. Both viral infectious diseases have distinctive clinical and laboratory features. Acute fever, vomiting, weakness, thrombocytopenia, and hemoconcentration that improve from day 5 after infection are typical symptoms of DHF in children. Complaints of fever, runny nose, cough, and pain when swallowing that usually occurs in COVID-19 also appeared. Medical investigations with serological tests for DHF and COVID-19 at the beginning of the COVID-19 pandemic can be used to diagnose these two infections because standard diagnostic tools using the PCR swab test cannot yet be performed. Symptomatic therapy for moderate degrees of these two viral infections is appropriate.